Flexibility of work relations: The intermittent employment contract - Damasceno, Julia Oliveira; Oliveira, Ana Maria Caldeira (Seven Editora, 2023)
Law 13,467/17, known as the Labor Reform, created a new form of employment contract, hitherto unheard of in the country: the Intermittent Labor Contract. This new institute was conceived by the federal government as a solution to unemployment and informality in labor relations. This article aims to analyze the situation of the Intermittent Employment Contract two years after its institution by the Labor Reform of 2017, as well as the latest updates on the subject. The qualitative methodology was used with the adoption of the research technique of content analysis of documents related to the generation of jobs in this period, as well as the first decisions of the courts regarding the matter. As a result, the study shows that the creation of the Intermittent Labor Contract did not fulfill what it promised, because in addition to creating a new way of making labor relations precarious, it did not generate the expected increase in jobs, nor did it reduce the levels of informal work. DOI:https://doi.org/10.56238/uniknowindevolp-118